UTILIZING WATTPAD APPLICATION TO IMPROVE THE STUDENTS’ SKILL IN WRITING NARRATIVE TEXT AT THE EIGHT GRADE OF SMP YAYASAN PERGURUAN KELUARGA PEMATANGSIANTAR 2020/2021 ACADEMIC YEAR - Amalia Tanjung, Dhara (Faculty of Tarbiyah nad Teacher Training, 2022)
The objective of this research is to improve students’ skill in writing in Narrative Text by utilizing the Wattpad Application at the eight grade students of Junior High School. In conducting the study, the researcher involved the English teacher, the school principal, and the students at the second grade of Senior High School especially VIII-1 class. This research conduct at SMP Yayasan Perguruan Keluarga Pematangsiantar as the subject of researcher. The subject of this research were consisted of 25 students. The research conduct with classroom action research. In conducting this action research, the researcher divided the action into two cycles. The researcher collaborated with English teacher in implementing the actions. The data of this study were mostly qualitative although there were some quantitative data. The qualitative data were from observation sheet, interview transcripts, and documentation,. While the quantitative data were from Pre-Test, Post-Test I and Post-Test II, The result of students’ score shows that the students’ average score keep improving in every test. The students’ average score in pre-test was 57.7, There were 2 students (8 %) who passed the Minimum Mastery criterion (75). In the Post-tTst in cycle I, there was 10 students (40%) who passed the score 75. In the Post-Test in cycle II there was 22 students (81.8%) who passed the Minimum Mastery criterion (75). Based on the quantitative data above, it can be seen that the students’ score showed the improvement from the first to the last test. Furthermore, the qualitative data showed that all the learning activities gave contributions not only improved the students’ skills in writing Narrative Text but also the students’ confidence, interest, enthusiasm, and motivation.